Wahdat al-Wujūd in Sufi Thought: Bridging Metaphysical Unity and Mystical Devotion - Dr. Syed Hamid Farooq Bukhari; Dr. Naseem Akhter (الآفاق اسلامی و تحقیقی مجلہ)
This paper explains the Wahdat al-Wujūd (Unity of Being) doctrine, a pivotal metaphysical idea in traditional Sufi philosophy, maintaining the oneness of existence and ontological derivation of all that exists from the Divine. Based on the philosophy of Ibn 'Arabi (d. 1240) and developed by his disciples, this idea is one of the most significant and debated articulations in Islamic mysticism. The work traces its philosophical origins in early Sufi definitions and its systematic articulation in the intellectual climate of Andalusia and the wider Islamic world. Though historically treated as a speculative metaphysical system, Wahdat al-Wujūd at the same time was a working spiritual framework, which influenced devotional exercises like dhikr, fana', and murāqabah, and formed the ethical and psychological conversion of the Sufi aspirant. Through analysis of both philosophical works and devotional language, especially poetry and ritual, the paper underscores the integrating dimension of the doctrine, whereby metaphysical speculation is rendered concrete through lived mystical experience. Additionally, the article places Wahdat al-Wujūd in current academic debates, discussing its continued relevance, reinterpretations, and criticisms, particularly concerning pluralism, comparative mysticism, and changing debates around orthodoxy. Finally, this study contributes to a nuanced understanding of how classical Sufism bridged the abstract and the experiential, providing a coherent vision of the Real that remains evocative across spiritual and intellectual domains.